The Effect of Fertilizers on Some Growth and Physiological Aspect of Chili Cultivar: a review - Pangestu, Prestiani Yulia; Marta, Fadhillah; Eskundari, Ratna Dewi; Hanik, Nur Rokhimah; Purwanto, Agus (MultiTech Publisher, 2024)
Chili is a type of plant that is consumed almost every day by almost all of the world's population. Increasing the yield of chili plants will ensure the availability of chilies on the market. One effort to increase the amount of chili production is by choosing the right fertilizer based on the type of chili planted. In this review article, we discuss the influence of chemical and or non-chemical fertilizer types which are related to physiological aspects, for example the number of leaves, plant height, and total chlorophyll content. By knowing a lot of information regarding fertilization of chili plants, it is hoped that it can help in efforts to increase production so that it can meet people's needs for chilies.